Novel anti-EPHA2 antibody, DS-8895a for cancer treatment. Issue 11 (1st November 2016) - Hasegawa, Jun; Sue, Mayumi; Yamato, Michiko; Ichikawa, Junya; Ishida, Saori; Shibutani, Tomoko; Kitamura, Michiko; Wada, Teiji; Agatsuma, Toshinori
ABSTRACT: Overexpression of EPHA2 has been observed in multiple cancers and reported to be associated with poor prognosis. Here, we produced an afucosylated humanized anti-EPHA2 monoclonal antibody (mAb), DS-8895a for cancer treatment. The antibody recognizes the extracellular juxtamembrane region of EPHA2 and therefore can bind to both full-length and truncated forms of EPHA2, which are anchored to cell membranes and recently reported to be produced by post-translational cleavage in tumors. DS-8895a exhibited markedly increased antibody dependent cellular cytotoxicity (ADCC) in vitro and also inhibited tumor growth in EPHA2-positive human breast cancer MDA-MB-231 and human gastric cancer SNU-16 xenograft mouse models. Moreover, DS-8895a in combination with cisplatin (CDDP) showed better efficacy than each of the monotherapies did in the human gastric cancer model. These results suggest that a novel antibody, DS-8895a has therapeutic potential against EPHA2-expressing tumors.